Cycloartane Triterpenoids with Anti-melanin Deposition Activity - Nugroho, Alfarius Eko; Matsumoto, Misaki; Sotozono, Yayoi; Kaneda, Toshio; A. Hadi, A. Hamid; Morita, Hiroshi (SAGE Publications, 2018)
Bioactivity guided separation of the extract of Malaysian Garcinia sp. resulted in the isolation of 23-acetoxy-mangiferonic acid (1) and the absolute configuration of C-23 was elucidated to be R by the advanced Mosher's method. The anti-melanin deposition activity of 1 was caused by the down regulation of tyrosinase gene expression.